Ab initio study on optical properties of glycine sodium nitrate: a novel semiorganic nonlinear optical crystal. Issue 110 (22nd October 2015) - Dadsetani, M.; Omidi, A. R.
Abstract : The electronic structure, and linear and nonlinear optical susceptibilities of crystalline glycine-sodium nitrate (GSN) has been studied using the full potential linear augmented plane wave method within density-functional theory. Abstract : The electronic structure, and linear and nonlinear optical susceptibilities of crystalline glycine-sodium nitrate (GSN) has been studied using the full potential linear augmented plane wave method within density-functional theory. In addition, we have investigated the excitonic effects by means of the bootstrap exchange–correlation kernel within time dependent density functional theory. The crystal in question has a band structure with low dispersion which is a characteristic behavior of molecular crystals. Findings show that the inorganic nitrate group plays a major role in enhancing the optical response of this semi-organic crystal. Although, GSN shows a smaller nonlinear response, in comparison with organic crystals, it has a wide range of transparency as well as sufficient anisotropy, which make it a promising crystal for nonlinear applications. This study show that χ (2) yyx is more important in the infrared region of the spectra, while χ (2) yzy possesses the dominant peak in ultraviolet region. In addition to the high potential of excitonic effects, the investigated crystal shows extremely small wavelengths of plasmon peaks.